Using of the warm blood cardioplegia in cardio valve replacement - A. Klantsa; O. Terekhivska (Ukrainian Journal of Cardiovascular Surgery, 2018)
The purpose of the work is to evaluate the protection of the myocardium using intermittent antegrade, warm blood car-dioplegia in comparison with pharmacold cardioplegia under the conditions of artificial blood circulation.Materials and methods. The study was based on the patients who had aortic or mitral valve replacement under the condi-tions of artificial blood circulation in 2016–2017. We observed about 80 patients in the first group (in which we used warm blood cordioplegia as the cardioprotection method), and 80 patients in the second category (for whom we used crystalloid cold cardioplegia). Selection and distribution of patients in the groups was done randomly. We analyzed the frequency of cardioversion use after reperfusion, the number of spontaneous cardiac rhythm restora-tions, creatine phosphokinase-MB levels, transaminase levels, and the need for inotropic support during the early postop-erative period. Laboratory and instrumental studies were performed during the first two days after cardiac surgery.Results. Despite the technically more complicated process of conducting warm blood cardioplegia, the following ben-efits have been identified: in the first group we identified a lower number of patients for whom cardioversion after reperfu-sion was used; atrioventricular blockade of ІІ–ІІІ degrees, requiring additional cardiac pacing, was registered with the same frequency; the number of patients who needed inotropic support in the early days was significantly higher in the second group; the average length of stay in the intensive care ward was (24±8 hours) for the first group of study and up to (29±7 hours) for the second group. The damage to the myocardium was lower in the first group, which correlated with significant differences in the levels of creatine phosphokinase-MB.